2020
DOI: 10.1021/acsomega.0c00155
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles Using Cucumis prophetarum Aqueous Leaf Extract and Their Antibacterial and Antiproliferative Activity Against Cancer Cell Lines

Abstract: Biosynthesized nanoparticles are gaining attention because of biologically active plant secondary metabolites that help in green synthesis and also due to their unique biological applications. This study reports a facile, ecofriendly, reliable, and cost-effective synthesis of silver nanoparticles using the aqueous leaf extract of Cucumis prophetarum (C. prophetarum) and their antibacterial and antiproliferative activity. Silver nanoparticles were biosynthesized using the aqueous leaf extract of C. prophetarum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
137
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(184 citation statements)
references
References 44 publications
15
137
1
Order By: Relevance
“…The cytotoxicity of AgNPs against MCF-7 cells was also reported in several articles. 1 , 41 , 44 , 48 , 51 , 52 , 54 However, the long-term effect of Ag/AgCl-NPs on MCF-7 cell line was not reported. In the present study, the colony of MCF-7 cells was not observed in the synthesized Ag/AgCl-NP-treated wells after two weeks as compared with the non-treated wells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of AgNPs against MCF-7 cells was also reported in several articles. 1 , 41 , 44 , 48 , 51 , 52 , 54 However, the long-term effect of Ag/AgCl-NPs on MCF-7 cell line was not reported. In the present study, the colony of MCF-7 cells was not observed in the synthesized Ag/AgCl-NP-treated wells after two weeks as compared with the non-treated wells.…”
Section: Discussionmentioning
confidence: 99%
“…It has extensive applications in numerous sectors like food, biomedicine, agriculture, and cosmetic industries that have arisen as one of the huge arenas of research. [1][2][3] At present, the synthesis of plant-mediated metal (Ag, Au, Zn) nanoparticles is the main point of attraction among current researchers due to its unique characteristics higher optoelectronic property, and biocompatibility. [2][3][4] Biosynthesis methods are recently used to synthesize nanoparticles by utilizing natural (reducing, capping, and stabilizing) agents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] At present, the synthesis of plant-mediated metal (Ag, Au, Zn) nanoparticles is the main point of attraction among current researchers due to its unique characteristics higher optoelectronic property, and biocompatibility. [2][3][4] Biosynthesis methods are recently used to synthesize nanoparticles by utilizing natural (reducing, capping, and stabilizing) agents. [4][5][6] Using plant material synthesis of metal NPs like AgNPs is a non-toxic, harmless, economical, and eco-friendly method of nanoparticle synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Cucumis prophetarum A549 105.80 Hemlata et al [69] MDA explains the % cell toxicity profile of the extract and nanoparticles. The AgNPs have 100% toxicity at 25 μg ml −1 concentration, and the IC 50 value is found to be 3.6 μg ml −1 .…”
mentioning
confidence: 99%